Options for optimizing noninvasive respiratory support in the development of hypoxemic acute respiratory failure - A. G. Koryakin; A. V. Vlasenko; E. P. Rodionov; V. I. Makovey; V. V. Erofeev; S. A. Osipov; E. A. Evdokimov (Вестник анестезиологии и реаниматологии)
Introduction. Acute respiratory failure (ARF) remains one of the most relevant problems of modern medicine and intensive care, and respiratory support (RS) remains the indispensable method of temporary external respiratory function replacement. Despite of widespread use of non-invasive ventilation (NIV) in clinical practice, at present systematic scientific data about possibilities for optimizing the use of these methods of RS in patients with hypoxemic ARF development is absent. It can be assumed that the combination of mask NIV and high-flow oxygen therapy (HFOT) at the stage of ARF development can improve results of treatment in this group of patients.The objective was to improve the results of treatment in patients with hypoxemic ARF through the combined use of mask NIV and HFOT.Materials and methods. The prospective cohort study included 77 patients aged 46.8 ± 11.8 years. Patients were randomized into three groups: in group A, RS was performed by using NIV and traditional low-flow oxygen therapy, in group B – by using HFOT, in group C – by sequential combination of NIV sessions and HFOT. The groups compared gas exchange rates, RS duration, intubation rate and nosocomial pneumonia (NP) incidence, length of treatment in the intensive care unit (ICU) and hospitalizations, overall mortality, and prognostic factors for tracheal intubation were also studied.Results. The combination of mask NIV and HFOT was found to be more clinically effective compared to their separate use. Combination of mask NIV and HFOT had the best effect on gas exchange rates in the long term period, reduced RS duration, intubation rate and pneumonia incidence, ICU treatment duration. Risk factors for tracheal intubation were revealed: RS duration more than 4.5 days, intra-abdominal pressure (IAP) more than 18 cm of water.Conclusions. The combination of mask NIV and HFOT increases the therapeutic potential of each of these RS methods and improves the results of treatment in patients with hypoxemic ARF development.